Structural, optical, room-temperature and low-temperature magnetic properties of Mg–Zn nanoferrite ceramics. Issue 1 (2nd January 2019) - Kumar, D. Ravi; Ahmad, Syed Ismail; Lincoln, Ch. Abraham; Ravinder, D.
ABSTRACT: Mg–Zn nanocrystalline ferrites (Mg1− x Znx Fe2 O4, where x = 0.0 to 1.0) were synthesized by the citrate gel auto-combustion route. XRD revealed the formation of nano-sized particles with cubic spinel structure. Lattice constant and specific surface area increased with Zn substitution. SEM micrographs revealed inhomogeneous grains with agglomerates; EDS spectra confirmed the stoichiometry. HRTEM images showed agglomerated nanoparticles with average particle sizes of 21 nm and 16 nm for x  = 0.6 and 1.0, respectively, and lattice fringe images and SAED patterns showed nanocrystalline characteristics corroborating the XRD results. FTIR and Raman spectra recorded at room temperature confirmed the spinel structure of ferrites. VSM technique at room temperature used to measure magnetic properties. MS and HC were found to decrease with increases in the Zn concentration in Mg–Zn ferrites due to a weakening of the A–B interaction and decrease in the particle size and surface effect. Low-temperature magnetic studies were carried out in the ZFC and FC modes using SQUIDS by applying 100 Oe between temperatures of 5 and 400 K, and magnetic isotherms were recorded at temperatures of 51 and 310 K. The study revealed the superparamagnetic nature of the synthesized samples showing that the blocking temperature ( T B ) depends on interparticle interactions.